2008
DOI: 10.1111/j.1745-9125.2008.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

A Reappraisal of the Overlap of Violent Offenders and Victims*

Abstract: Because research shows a close association between offending and victimization, recent work has argued that theories that account for crime should explain victimization as well. The current study uses a new approach to examine the extent of the overlap between offenders

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
196
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(210 citation statements)
references
References 56 publications
13
196
0
1
Order By: Relevance
“…For example, Singer demonstrated that within subcultures of violence, individuals who have attacked and victimized others risk retaliation from former victims [3]. Additional research examining violence among women in Philadelphia [11] and disorganized communities in both Philadelphia [12] and St. Louis [13] have since corroborated Singer's earlier findings.…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…For example, Singer demonstrated that within subcultures of violence, individuals who have attacked and victimized others risk retaliation from former victims [3]. Additional research examining violence among women in Philadelphia [11] and disorganized communities in both Philadelphia [12] and St. Louis [13] have since corroborated Singer's earlier findings.…”
Section: Introductionsupporting
confidence: 68%
“…Therefore, other theories have expanded routine activity/lifestyles theory to provide this perspective [3]. Causal perspectives associated with this theoretical framework suggest that unstructured activity away from authority figures increases opportunities to engage in criminal activities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations